Concept of Romanization in Archaeology: Rise and Fall of a Paradigm - Vladimir D. Mihajlović (University of Belgrade, 2016)
From the foundation of the discipline of archaeology, the study of the Roman provinces has been under the decisive influence of the concept of Romanization, itself developed under the specific social conditions of Europe by the end of the 19th and beginning of the 20th century. Romanization has been the general interpretive framework in explaining the changes in the local communities induced by the Roman rule, presupposing the normative approach to the Roman culture, often valued favorably in contrast to the local cultures. The theoretical developments in the field of classical archaeology, taking place by the end of the 20th century, have contributed to the reconsideration and abandonment of the basic assumptions of the idea of Romanization. After this period, in the Roman provincial archaeology efforts have been concentrated to define new, more theoretically sound approaches to changes induced by the expansion of the Roman imperialism. The paper presents the critical overview of the theoretical discussions in the field of the Roman provincial archaeology, starting from the critique of the concept of Romanization to the newly established interpretive framework offering different possibilities for future investigation of these issues.